2017
DOI: 10.1055/s-0043-117611
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperglycaemic Effect of Cleome Rutidosperma in Alloxan-Induced Diabetic Albino Rats

Abstract: The hypoglycaemic and antihyperglycaemic effects of methanol extract of leaves of Cleome rutidosperma (Cr) DC (Family: Capparidaceae) was investigated in Wistar rats. Fifty normoglycaemic male rats (120 g-200 g) were divided into groups A (hypoglycaemic study; n=20) and B (antihyperglycaemic study; n=30). Each experiment had one control group and three groups administered with Cr (100, 200 or 400 mg/kg) respectively. Group B had two additional groups of diabetic-untreated rats and glibenclamide-treated diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…One in vivo study found that administration of aqueous leaf extract of the plant to streptozotocin-diabetic rats enhanced the activity of hepatic glucokinase and inhibited glucose-6-phosphatase (gluconeogenesis enzymatic activity) [31]. The hypoglycaemic and antihyperglycaemic activities of the plant were studied in alloxan diabetic rats [35]. In the model, methanol extract of the plant's leaves at the dose of 200 mg/kg presented stronger glycemic control in comparison with glibenclamide.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…One in vivo study found that administration of aqueous leaf extract of the plant to streptozotocin-diabetic rats enhanced the activity of hepatic glucokinase and inhibited glucose-6-phosphatase (gluconeogenesis enzymatic activity) [31]. The hypoglycaemic and antihyperglycaemic activities of the plant were studied in alloxan diabetic rats [35]. In the model, methanol extract of the plant's leaves at the dose of 200 mg/kg presented stronger glycemic control in comparison with glibenclamide.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…The uses of herbal products have been established for treatment of various type of illness [7] and it also has been long history for 5000 years ago, Iranian traditional medicine has long story and well expressed in Avicenna s book (canon) [8,9]. The plant C. oxyacantha is one the medicinal plants which grow in Mediterranean temperate regions [10], the plant has various traditional application including wound healing and anti-inflammatory effect [10].…”
Section: Introductionmentioning
confidence: 99%